Blast of Silence - Salt, Waldo 1914-1987; Kupferman, Meyer (The Criterion Coll., 2008)
Frankie Bono is an orphan who has learned to make a profitable living as a contract killer. Traveling from Cleveland to New York during the Christmas season, he is charged with taking out mid-level Harlem numbers and drug kingpin Troiano. Stalking his prey as he goes about his daily routine, Bono is distracted by an unexpected encounter with a childhood friend whose sister sees him as a lonely man, not the barely human shell he has become. Acutely aware of his own mortality, Bono sees everything as a facade, the pretty Christmas lights mere glitzy decorations covering the festering rot of existence, and his own personal hell.
Aspect ratio 1:1.33, 16:9 widescreen. - New, restored digital transfer
Orig.: USA 1961
Enth. "Requiem for a killer: The Making of 'Blast of silence'" ; rare on-set Polaroids ; photos of locations in 2008 ; a booklet featuring an essay by film critic Terrence Rafferty and a four-page graphic-novel adaptation of the film by acclaimed artist Sean Phillips
Keywords: Assassins - New York (State) - New York - Drama; Christmas - New York (State) - New York - Drama; Gangs - New York (State) - New York - Drama; Assassins -- New York (State) -- New York -- Drama; Christmas -- New York (State) -- New York -- Drama; Gangsters -- New York (State) -- New York -- Drama; Manhattan (New York, N.Y.) - Drama; Manhattan (New York, N.Y.) -- Drama; Feature films; Fiction films; Film noir; Gangster films; Thrillers (Motion pictures); Video recordings for the hearing impaired; Crime - Feature; Film noir - Feature; Gangster - Feature